Employees' Perception of HRD Climate in Commercial Bank of Ethiopia - Kanamarlapudi, Anil Kumar; Vangapandu, Rama Devi (Prabandhan: Indian Journal of Management, 2013)
People are the assets and constitute the source of competitive advantage for the organizations. Acquiring the right people, facilitating their development, and retaining them can bring in tangible and intangible positive results for the organization. An organization that wants to sustain and grow has to enable continuous development of competencies in people through conducive human resource development (HRD) climate. The main objective of this paper is to study the effectiveness of the human resource development (HRD) climate in Commercial Bank of Ethiopia in the sample branches of Diredawa district as perceived by its employees. The HRD climate in Commercial Bank of Ethiopia was measured using the HRD climate survey, which contains 38 items. The results revealed that the overall percentile of the HRD climate in Commercial Bank of Ethiopia was 63.75, indicating the presence of a 'good' HRD climate in the examined branches of the Commercial Bank of Ethiopia. Factor analysis was also used to identify the main factors affecting the HRD climate in Commercial Bank of Ethiopia.